Two di- and trinuclear Gd(III) clusters derived from monocarboxylates exhibiting significant magnetic entropy changes. (10th January 2017) - Liu, Sui-Jun; Yao, Shu-Li; Cao, Chen; Zheng, Teng-Fei; Liu, Cao; Wang, Zheng-Xiang; Zhao, Qiang; Liao, Jin-Sheng; Chen, Jing-Lin; Wen, He-Rui
Graphical abstract: Two carboxylate-bridged Gd2 and Gd3 cluster complexes have been prepared under hydrothermal conditions. They show significant and distinct magnetic entropy changes, mainly influenced by magnetic densities. Abstract: Two di- and trinuclear Gd(III) clusters with the formulas [Gd2 (omba)6 (phen)2 ]·2H2 O (1 ) and [Gd3 (Hsa)5 (sa)2 (phen)3 ] (2 ) (Homba = o -methoxybenzoic acid, H2 sa = salicylic acid and phen = 1, 10-phenanthroline) have been prepared through the hydrothermal reactions. Complex1 takes a dinuclear structure and two Gd(III) are bridged by two syn - syn - μ 2 - η 1 : η 1 and two syn - syn - μ 2 - η 1 : η 2 carboxylates. While complex2 is a trinuclear cluster linked by one syn - syn - μ 2 - η 1 : η 2 and two syn - syn - μ 2 - η 1 : η 1 carboxylates. Magnetic studies reveal the key impact of magnetic density on the magnetocaloric effect in Gd(III) systems. They exhibit relatively weak magnetic interactions and significant magnetic entropy changes with −Δ S m max = 17.1 J kg −1 K −1 and 22.5 J kg −1 K −1 ( T = 2 K, Δ H = 7 T), respectively.